KINERJA KEUANGAN: KEPATUHAN WAJIB PAJAK DAN INSENTIF PAJAK DENGAN UKURAN PERUSAHAAN SEBAGAI VARIABEL MODERASI PADA SEKTOR MAKANAN DAN MINUMAN - Puspita Maelani; Muthia Ulfa; Birrul Walidain (Jurnal Akuntansi, Keuangan dan Teknologi Informasi Akuntansi, 2026)
This study aims to analyze the effect of tax compliance and tax incentives on financial performance with company size as a moderating variable in the food and beverage sector companies listed on the Indonesia Stock Exchange for the 2020–2024 period. The research method used is an associative quantitative method with secondary data obtained from the companies' financial reports. The research sample was determined using a purposive sampling technique, resulting in 20 companies with a total of 100 observations. Data analysis was conducted through descriptive statistics, multiple linear regression, and Moderated Regression Analysis (MRA). The results of the study indicate that tax compliance has a negative and significant effect on financial performance, while tax incentives have a positive and significant effect on financial performance. In addition, company size is unable to moderate the effect of tax compliance on financial performance or the effect of tax incentives on financial performance. The conclusion of this study shows that increasing tax compliance tends to decrease financial performance in the short term due to the increasing tax burden, while the use of tax incentives can improve financial performance through fiscal efficiency, and company size does not act as a moderating variable in this relationship. Keywords: Financial Performance, Tax Compliance, Tax Incentives, Company Size, Moderated Regression Analysis (MRA